17. If P (A) = a, P (B) = b and P (P (A, B) = c then the expression of P (A’ B’) in terms of a, b and cis (a) 1-a-b-c (b) a +

Question

17. If P (A) = a, P (B) = b and P (P (A, B) = c then the expression of P (A’ B’) in terms of a, b and
cis
(a) 1-a-b-c
(b) a + b c
(d) 1 – a – b + c
(c) 1 + a-b-c​

in progress 0
Alexandra 1 month 2021-08-15T09:54:25+00:00 1 Answer 1 views 0

Answers ( )

    0
    2021-08-15T09:55:38+00:00

    Answer:

    ur answer is (a) according to me

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )